The rapid mass calorimeter: Understanding reduced-scale fire test results. (February 2017) - Rabe, Sebastian; Schartel, Bernhard
Abstract: The effects of reducing specimen size on the fire behavior of polymeric materials were investigated by means of the rapid mass calorimeter, a high-throughput screening instrument. Results from the rapid mass calorimeter were compared with those from the cone calorimeter. Correlation coefficients between the different measures of each method and between the two methods are discussed to elucidate the differences and similarities in the two methods. Materials with characteristic heat release rate (HRR) curves in the cone calorimeter were evaluated in detail. The rapid mass calorimeter produces valuable and interpretable results with HRR curve characteristics similar to cone calorimeter results. Compared to cone calorimeter measurements, material savings of 96% are achieved, while maintaining the advantages of a macroscopic fire test.